2011
DOI: 10.2478/v10035-011-0041-5
|View full text |Cite
|
Sign up to set email alerts
|

Local Anesthesia in Thyroid Surgery - Own Experience and Literature Review

Abstract: The local anesthesia in thyroid surgery is rarely used, only in selected patients. Majority of centers performing thyroid surgery with local anesthesia have possibility to convert to the general anesthesia. the aim of the study was to present our experiences with partial thyroidectomy under local anesthesia performed in 49 consecutive subjects in the Central African Republic (bilateral subtotal strumectomy, total resection of the one lobe, subtotal resection of the one lobe). Material and methods. All admitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 17 publications
1
10
0
5
Order By: Relevance
“…Under local anaesthesia complication of general anaesthesia like hazards of endotracheal complication, side effects of anaesthetics, injury to recurrent laryngeal nerve can be avoided. Injury to recurrent laryngeal nerve can be avoided by voice monitoring during operation under local anesthesia as well as cardiac changes 4,11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under local anaesthesia complication of general anaesthesia like hazards of endotracheal complication, side effects of anaesthetics, injury to recurrent laryngeal nerve can be avoided. Injury to recurrent laryngeal nerve can be avoided by voice monitoring during operation under local anesthesia as well as cardiac changes 4,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Local anaesthesia avoids complication of general anaesthesia like nausea, vomiting in post operative period, causes rapid recovery from the operation 3 . Local anaesthesia is cost effective, easy to administer, less hospital stay and less complication 4 . Many studies reported thyroidectomy under local anaesthesia where general anaesthesia had high risk.…”
Section: Introductionmentioning
confidence: 99%
“…Thus surgeons started reverting towards regional anesthesia for thyroidectomy as it offered more safety, fast postoperative recovery and minimum hospital stay. 8 Many international studies reported that patients at high risk from general anesthesia underwent successful thyroidectomy under local anesthesia with minimum postoperative complications. Keeping in view the significance and advantages of local versus general anesthesia, for the last one decade the idea to use localized anesthesia for thyroid surgeries has been continuously revisited.…”
Section: The Study Population Included 81 Females and 19 Males With Tmentioning
confidence: 99%
“…[25][26][27] Furthermore, thyroidectomy under local anesthesia has been shown to be safe and effective in resource-poor settings with limited facilities for general anesthesia. [28][29][30][31] There was also no case of symptomatic hypocalcemia in the series, though some other studies showed hypocalcemia to be the most common morbidity post thyroidectomy. 7,[32][33][34] Zero incidence of hypocalcemia may have been due to the very few cases of total thyroidectomy in the study.…”
Section: Discussionmentioning
confidence: 99%